2019
DOI: 10.3758/s13428-019-01214-4
|View full text |Cite
|
Sign up to set email alerts
|

Do your eyes give you away? A validation study of eye-movement measures used as indicators for mindless reading

Abstract: Identifying eye-movement measures as objective indicators of mind wandering seems to be a work in progress. We reviewed research comparing eye movements during self-categorized episodes of normal versus mindless reading and found little consensus regarding the specific measures that are sensitive to attentional decoupling during mind wandering. To address this issue of inconsistency, we conducted a new, high-powered eye-tracking experiment and considered all previously identified mindwandering indicators. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 60 publications
5
47
0
2
Order By: Relevance
“…Although mind wandering probes do not interfere much with task performance, at least during simple cognitive tasks (Wiemers & Redick, 2018), they still interrupt the ongoing task and thus alternative indicators of mind wandering are needed (cf. Steindorf & Rummel, 2019). Different mind wandering indicators have been suggested, such as changes in response time variabilities , changes in pupil dilation , or changes in neural activity (Christoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although mind wandering probes do not interfere much with task performance, at least during simple cognitive tasks (Wiemers & Redick, 2018), they still interrupt the ongoing task and thus alternative indicators of mind wandering are needed (cf. Steindorf & Rummel, 2019). Different mind wandering indicators have been suggested, such as changes in response time variabilities , changes in pupil dilation , or changes in neural activity (Christoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies have not been entirely consistent on this measure. Some studies reported that MW was associated with fewer fixations during reading and scene perception (Faber et al, 2020;Krasich et al, 2018), whereas other reported no difference (Uzzaman & Joordens, 2011), or even more fixations during MW Steindorf & Rummel, 2020). A similar mixture of findings has been reported for fixation duration.…”
Section: Aggregated Measuresmentioning
confidence: 70%
“…It is worth noting that fewer and longer fixations were not consistently associated with MW in many previous studies (e.g., Faber et al, 2020;Smilek et al, 2010;Steindorf & Rummel, 2020;Uzzaman & Joordens, 2011). While some of the discrepancies might reflect a power issue, the specific task setting may also modulate the relationship between eye movements and MW.…”
Section: Aggregated Measuresmentioning
confidence: 83%
See 2 more Smart Citations